IMPLEMENTASI KEBIJAKAN PENGELOLAAN ASET DAN BARANG MILIK NEGARA DI IPDN KAMPUS JATINANGOR : Array - Agus Zakaria; and (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The implementation of policies for managing state assets and assets at the Institute for Internal Administration of the Jatinangor Campus has experienced several problems that have made its implementation not yet optimal. These problems have an impact on every stage of the management of state assets and assets, namely planning, administration, maintenance and processing, monitoring and evaluation as well as reporting of state-owned equipment and goods. Qualitative research methods will be used to analyze these problems. The purpose of this research is to analyze how the implementation of the policies for managing State Assets and Assets in IPDN Jatinangor Campus. The problems faced by the Equipment and Management Section of State Property are the lack of good communication in the implementation of policies for managing assets and assets owned by the state, lack of apparatus resources, there are still unscrupulous users of state property. and state property and bureaucratic structures that still need to be repaired and restructured in order to optimize the performance and distribution of tasks for managing state assets and assets in IPDN